Konsep Dan Metode Pendidikan Anak Menurut Luqman Al-Hakim Dalam Surah Luqman Ayat 12-19 - M. Afdi Maulana (Journal of Sustainable Education, 2026)
Children’s education is a fundamental responsibility that cannot be overlooked, particulary in shaping a generation that is faithful, knowledgeable, and morally upright. The Al-Qur’an, as a guide for Muslims, provides comprehensive guidance on the concepts and methods of children’s education, one of which is through the story of Luqman Al-Hakim in Surah Luqman verses 12-19. This study aims to examine in depth the concepts and methods of children’s education contained in the Al-Qur’an Surah Luqman verses 12-19, focusing on the exemplary figure of  Luqman Al-Hakim as a wise educator. This research employs a libary research method with a descriptive qualitative approach and tarbawi tafsir analysis. Primary data sources include the Al-Qur’an, Tafsir Ibn Kathir, and Tafsir Al-Misbah by M. Quraish Shihab, while secondary sources consist of scientific journals, Islamic education books, and relevant academic works. The results indicate that Luqman Al-Hakim applied three main educational principles: (1) akidah/tauhid education, (2) syariah/worship education, and (3) moral/akhlak education. The methods employed include the method of advice (mau’izhah), the method of exemplary conduct (uswah), and the method of parables (amtsal). Luqman Al-Hakim’s educational concept is proven to be comprehensive and holds high relevance to the development of student character in the context of modern Islamic Religious Education, making it a valuable reference for educator and parent alike.